2000
DOI: 10.1080/135062800407202
|View full text |Cite
|
Sign up to set email alerts
|

Priming of popout: III. A short-term implicit memory system beneficial for rapid target selection

Abstract: The priming of popout (PoP) (Maljkovic & Nakayama, 1994, 1996 increases the speed of attentional deployment to subsequent targets having the same feature characteristic and relative position, it lasts for approximately 5-8 trials, and is cumulative. Here we establish PoP as an example of short-term implicit memory by showing that it is qualitatively different from explicit memory. Using a postcued recall procedure embedded in the stream of search task trials, we show that explicit memory is not selective as is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
145
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(161 citation statements)
references
References 34 publications
12
145
2
2
Order By: Relevance
“…Studies of contextual cuing generally find that there is limited awareness of repeated display configurations (Schmitter-Edgecombe & Nissley, 2002), although awareness of repeated display configurations can reduce the magnitude of the contextual cuing effect (Howard et al, 2004). Previous investigations of singleton discrimination, however, using procedures similar to ours, have found that explicit memory for the color of a singleton does not last more than a single trial, whereas repetition priming effects last approximately 5-8 trials (Maljkovic & Nakayama, 2000). In addition, the magnitude of repetition priming in singleton discrimination does not appear to be influenced by awareness of the repetition pattern (Maljkovic & Nakayama, 1994).…”
Section: Methods Participantsmentioning
confidence: 54%
“…Studies of contextual cuing generally find that there is limited awareness of repeated display configurations (Schmitter-Edgecombe & Nissley, 2002), although awareness of repeated display configurations can reduce the magnitude of the contextual cuing effect (Howard et al, 2004). Previous investigations of singleton discrimination, however, using procedures similar to ours, have found that explicit memory for the color of a singleton does not last more than a single trial, whereas repetition priming effects last approximately 5-8 trials (Maljkovic & Nakayama, 2000). In addition, the magnitude of repetition priming in singleton discrimination does not appear to be influenced by awareness of the repetition pattern (Maljkovic & Nakayama, 1994).…”
Section: Methods Participantsmentioning
confidence: 54%
“…It is highly unlikely that participants consciously remembered up to eight previous trials and adjusted their attentional set accordingly in a top-down fashion. Indeed, Maljkovic and Nakayama (2000) showed that participants have no explicit memory for any but the immediately preceding trial (see also Mü ller, Krummenacher, & Heller, 2002, for similar conclusions). Moreover, in our experiment almost all participants reported that they had attempted to ignore the color and orientation information.…”
Section: Automatic or Top-down Controlled?mentioning
confidence: 92%
“…The repetition priming effects just described have been shown to be brief in duration, with the features of the tar-get affecting RTs significantly only for lags of a few trials (Maljkovic & Nakayama, 2000). In contrast, a long-term priming effect in visual search has been demonstrated by Chun and Jiang (1998).…”
Section: Priming In Visual Searchmentioning
confidence: 93%